One-Pot AgOAc-Mediated Synthesis of Polysubstituted Pyrroles from Primary Amines and Aldehydes: Application to the Total Synthesis of Purpurone - Li, Qingjiang; Fan, Aili; Lu, Zhiyao; Cui, Yuxin; Lin, Wenhan; Jia, Yanxing (Organic letters, 2010)
A simple and efficient method for the synthesis of 1,3,4-trisubstituted or 3,4-disubstituted pyrroles has been developed. The reaction represents the first time that pyrroles are synthesized directly from readily available aldehydes and amines (anilines) as starting materials. This method has been successfully applied to the rapid synthesis of purpurone.